REPERTOAR STRATEGI PENGEDEPANAN PASCAMODERNIS DALAM NOVEL ASMARALOKA - Pujiharto Pujiharto (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
One Indonesian novel which shows a new feature is Asmaraloka, written by Danarto. The aim of this article is to show the novel’s dominant characteristics on which the new feature is grounded. Based on the concept of foregrounded strategy of repertoire by Iser, I conclude that Asmaraloka presents some dominant characteristics of the ontological theme or the mode theme of the existence of the world. The modes of the existence of the world can be observed in the novel in that there are (1) boundary vagueness between the world of man and angel, (2) boundary vagueness between the world of man and the world of animal, (3) boundary vagueness between the world of man and the world of plant, (4) boundary vagueness between the world of man and the world of world objects, (5) boundary vagueness between the world of man and the world of animal, plant, and world object, (6) boundary transgression between the world of man and the world of Satan, (7) boundary vagueness between the world of man and the world of fairy tale, (8) emergence of the afterlife, (9) inserted zone, (10) the fight between the world of angel and the world of Satan, and (11) the dialogue between the angel with parts of human body. By revealing the diversity of the mode of the world, Asmaraloka presents plurality of the world.